-Dynamic representation of whisker deflection by synaptic potentials in spiny stellate and pyramidal cells in the barrels and septa of layer 4 rat somatosensory cortex - Brecht, Michael (Blackwell Science Inc, 2002)
Whole-cell voltage recordings were made in vivo from excitatory neurons (n = 23) in layer 4 of the barrel cortex in urethane-anaesthetised rats. Their receptive fields (RFs) for a brief whisker deflection were mapped, the position of the cell soma relative to barrel borders was determined for 15 cells and dendritic and axonal arbors were reconstructed for all cells. Three classes of neurons were identified: spiny stellate cells and pyramidal cells located in barrels and pyramidal cells located in septa. Dendritic and, with some exceptions, axonal arborisations of barrel cells were mostly restricted to the borders of a column with a cross sectional area of a barrel, defining a cytoarchitectonic barrel-column. Dendrites and axons of septum cells, in contrast, mostly extended across barrel borders. The subthreshold RFs measured by evoked postsynaptic potentials (PSPs) comprised a principal whisker (PW) and several surround whiskers (SuWs) indicating that deflection of a single whisker is represented in multiple barrels and septa. Barrel cells responded with larger depolarisation to stimulation of the PW (13.7 ± 4.6 mV (mean ± s.d.), n = 10) than septum cells (5.7 ± 2.4 mV, n = 5), the gradient between peak responses to PW and SuW deflection was steeper and the latency of depolarisation onset was shorter (8 ± 1.4 ms vs. 11 ± 2 ms). In barrel cells the response onset and the peak to SuW deflection was delayed depending on the distance to the PW thus indicating that the spatial representation of a single whisker deflection in the barrel map is dynamic and varies on the scale of milliseconds to tens of milliseconds. Septum cells responded later and with comparable latencies to PW and SuW stimulation. Spontaneous (0.053 ± 0.12 action potentials (APs) s(−1)) and evoked APs (0.14 ± 0.29 APs per principal whisker (PW) stimulus) were sparse. We conclude that PSPs in ensembles of barrel cells represent dynamically the deflection of a single whisker with high temporal and spatial acuity, initially by the excitation in a single PW-barrel followed by multi-barrel excitation. This presumably reflects the divergence of thalamocortical projections to different barrels. Septum cell PSPs preferably represent multiple whisker deflections, but less dynamically and with less spatial acuity.